Characterization of a recombinant arylsulfatase enzyme from glucosinolate-metabolizing human gut bacterium Escherichia coli VL8 - Luang-In, Vijitra; Rossiter, John T.; Albaser, Abdulhadi A. (Asia-Pacific Journal of Science and Technology, 2023)
Bacterial arylsulfatases can hydrolyze organosulfur compounds. Thus, the objective of this research project was to characterize a recombinant arylsulfatase (ARS) from Escherichia coli VL8, a human gut bacterium able to produce nitrile from desulfo-glucosinolates. The Ars gene (Accession no.: LC685335.1) with a length of 1,494 bp corresponding to ARS enzyme with a length of 497 amino acids was cloned from E. coli VL8 and expressed in E. coli BL21 (DE3) for 16 h at 25°C in lysogeny broth (LB) by induction of isopropyl β-D-1-thiogalactopyranoside (0.5 mM). The recombinant ARS enzyme (57 kDa) was partially purified using Ni2+ affinity column chromatography. This recombinant ARS enzyme was able to desulfate synthetic p-nitrocatechol sulfate (pNCS) substrate to produce p-nitrocatechol as an indicator of ARS activity, with optimal conditions at 30°C and pH 6.0, respectively. The ARS enzyme displayed a Michaelis-Menten kinetic constant (Km) of 1.09 mM and Maximum reaction velocity (Vmax) of 25.1 U/mg for pNCS. ARS enzyme activity toward pNCS was not enhanced by any metal ions, while activity was inhibited by Ca2+, Fe2+, NaHSO4 and Na2SO4.